2001
DOI: 10.1038/sj.onc.1204155
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and viral Fos proteins are degraded by different proteolytic systems

Abstract: c-Fos proto-oncoprotein is a short-lived transcription factor degraded by the proteasome in vivo. Its mutated forms expressed by the mouse osteosarcomatogenic retroviruses, FBJ-MSV and FBR-MSV, are stabilized two-and threefold, respectively. To elucidate the mechanisms underlying v-Fos FBJ and v-Fos FBR protein stabilization, we conducted a genetic analysis in which the half-lives and the sensitivities to various cell-permeable protease inhibitors of a variety of cellular and viral protein mutants were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…Pulsechase experiments, with a chase starting 1.5 h postserum addition, indicated a twofold stabilization of the c-FosDPEST3 protein with a half-life shift from 21+1 to 44+7 minutes ( Figure 2C). Because we have recently shown that the mutations carried by Fos proteins expressed from FBR-MSV and FBJ-MSV oncogenic retroviruses confer resistance to proteasomal degradation which is partially compensated by acquisition of sensitivity to another still-to-be-identi®ed protease (Acquaviva et al, 2001), it was important to investigate whether the three PEST deletion mutants were still subjected to proteasomal degradation. To this aim, synchronization experiments were conducted in the presence of the cell-permeant inhibitors chloroquine, which inhibits lysosomal proteases, E64D, which inhibits a variety of cysteine proteases and MG132, which is a potent inhibitor of the proteasome.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pulsechase experiments, with a chase starting 1.5 h postserum addition, indicated a twofold stabilization of the c-FosDPEST3 protein with a half-life shift from 21+1 to 44+7 minutes ( Figure 2C). Because we have recently shown that the mutations carried by Fos proteins expressed from FBR-MSV and FBJ-MSV oncogenic retroviruses confer resistance to proteasomal degradation which is partially compensated by acquisition of sensitivity to another still-to-be-identi®ed protease (Acquaviva et al, 2001), it was important to investigate whether the three PEST deletion mutants were still subjected to proteasomal degradation. To this aim, synchronization experiments were conducted in the presence of the cell-permeant inhibitors chloroquine, which inhibits lysosomal proteases, E64D, which inhibits a variety of cysteine proteases and MG132, which is a potent inhibitor of the proteasome.…”
Section: Resultsmentioning
confidence: 99%
“…Balb/c 3T3 cell c-fos mRNA was detected with a mouse-speci®c probe (Plasmid PM381 in ref. (Acquaviva et al, 2001) whereas the ectopic RNA was detected using the c-Fos DNA sequence constructed by Abate et al (1990).…”
Section: Electrophoresis Immunoblotting and Northern Blottingmentioning
confidence: 99%
See 3 more Smart Citations